SOSIALISASI PEMENUHAN GIZI ANAK USIA DINI MELALUI BEKAL KREASI DI KOBER AL-GHIFARI LAMPUNG TIMUR - Noormawanti Noormawanti; Annisa Nur Firdausyi; lusi marlisa; Prabowo Adi Widayat (Perkumpulan Pendidikan Islam Anak Usia Dini Wilayah Sumatera, 2022)
A supporting factor in the growth, development and optimization of the brain is a balanced nutritional intake that is fulfilled. Consuming instant food can make it difficult and difficult for children to eat healthy foods such as vegetables, so this will be a difficulty for parents and eventually force their children to eat vegetables. One of the efforts that can be made by parents is to familiarize children with healthy food Self-created lunches are guaranteed to be clean and can choose good quality ingredients. Preparation Stage The method used in this service activity carried out between lecturers and students is through several stages, namely observation, administration, preparation of tools and materials. The Evaluation Stage carried out is assistance in creating assistance using nutritional provision equipment, ensuring that target partners have been able to understand and practice independently and evaluating the impact of the results of socialization activities The results of the service carried out in carrying out the socialization of nutritional fulfillment there are 3 stages that partners need to do. The stages carried out in this assistance include: Determining an interesting theme on the lunch creations to be made, Choosing nutritious or good quality food ingredients, and Assistance in Decorating Lunch Creations Attractively.